Anticholinesterase activity and phenolic profile of two medicinal plants (Quassia undulata and Senecio abyssinicus) used in managing cognitive dysfunction in Nigeria. Issue 4 (10th January 2018) - Odubanjo, Veronica O.; Oboh, Ganiyu; Oyeleye, Sunday I.; Adefegha, Stephen A.
Abstract: Quassia undulata (QU) and Senecio abyssinicus (SA) leaves are known in folklore in the management of cognitive disorder in Nigeria. However, there is dearth of information about their mechanism of actions. In this study, the effect of QU and SA aqueous extracts on acetylcholinesterase (AChE) and butrylcholinesteras (BChE) activities were determined as well as their antioxidant capacity and phenolic constituents. The result showed that both extracts inhibited AChE and BChE activities and also exhibited antioxidant effect, however, extract from SA had the highest effect compared to that of QU. HPLC analysis revealed the presence of gallic, ellagic, caffeic, quercetin, rutin, and catechin. The inhibition of AChE and BChE activities, and antioxidant capacity of QU and SA could be among the mechanism of actions regarding their use in folklore for the management of cognitive dysfunction. These could therefore be linked to their richness in phenolic compounds, as SA extract exhibited higher effects. Practical applications: Many plants have been used traditionally in the treatment of various disorders owing to their bioactivity. The outcome of this research provides biochemical information to the folkloric use of Quassia undulate and Senecio abyssinicus in the management of neurodegenerative disorder, and also to the pharmacologist with an option to synthesize drugs with little or no side effects.